Environmental health: emancipatory care challenges and possibilities by the nurse - Marcela de Abreu Moniz; Donizete Vago Daher; Vera Maria Sabóia; Crystiane Ribas Batista Ribeiro (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objectives: to discuss challenges and possibilities for the construction of Environmental Health emancipatory care practices by the nurse. Methods: reflective analysis based on conceptual, theoretical, and methodological aspects of nursing care, under the emancipatory and critical perspective. Results: contemporary environmental issues involve complex determinants of the health-disease process. This fact requires the accomplishment of educative actions that encourage the change of environmental attitudes related to health-risk situations. In this sense, there are significant demands for emancipatory practices of primary care in Environmental Health by nurses, which need to be systematized by health and education institutions. Final considerations: the nurse, as an educator and social actor, should offer emancipatory practices of risk management, empowerment, and shared social and environmental responsibility, with a view to recovering an ecological well-being and social transformation, to improve environmental quality and human life.